2012
DOI: 10.1242/jeb.061838
|View full text |Cite
|
Sign up to set email alerts
|

Total recoil: perch compliance alters jumping performance and kinematics in green anole lizards (Anolis carolinensis)

Abstract: SUMMARY Jumping is a common form of locomotion for many arboreal animals. Many species of the arboreal lizard genus Anolis occupy habitats in which they must jump to and from unsteady perches, e.g. narrow branches, vines, grass and leaves. Anoles therefore often use compliant perches that could alter jump performance. In this study we conducted a small survey of the compliance of perches used by the arboreal green anole Anolis carolinensis in the wild (N=54 perches) and then, using perches withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 44 publications
1
43
0
Order By: Relevance
“…Compliance ( C ) was calculated using equation 1 [10], where dy is the change in displacement and dF is the given force. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compliance ( C ) was calculated using equation 1 [10], where dy is the change in displacement and dF is the given force. …”
Section: Methodsmentioning
confidence: 99%
“…In contrast, it has generally been found that branches have too much compliance to return energy to locomoting animals. The high compliance leads to low oscillatory frequencies, so when animals jump off branches they lose contact before the branch has time to recover [5], [9], [10]. The result is a reduced jumping performance and energy loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that, as in our laboratory study, green anoles jumped from compliant perches prior to recoil and did not use the energy stored in the perch for their jump (Gilman et al . ). Lastly, we found a significant negative relationship between perch diameter and compliance in most natural structures in the habitat; however, variability in compliance for a given diameter generally precludes the use of diameter as a proxy for compliance in this system.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, we performed laboratory trials on the effects of perch compliance on jumping kinematics and performance in A. carolinensis , and we found that increased compliance resulted in significantly shorter jump distances and lower take‐off velocities (Gilman et al . ). Because these lizards occupy habitats in which they must jump to and from compliant perches, our results suggest that perch compliance may be an important structural variable that influences how this species negotiates its habitat.…”
Section: Introductionmentioning
confidence: 97%